Unified throughout‐pore microstructure enables ultrahigh separator porosity for robust high‐flux lithium batteries - Dongjiang Chen; Yuanpeng Liu; Chao Feng; Yuhui He; Shengyu Zhou; Botao Yuan; Yunfa Dong; Haodong Xie; Guangfeng Zeng; Jiecai Han; Weidong He (Electron)
Abstract With small thickness, commercial polyolefin separators own low porosity to ensure sufficient thermomechanical properties, resulting in tortuous and enlarged Li+ diffusion pathways that induce large overpotentials and detrimental dendrite growth. As a dilemma, the exploration of highly porous separators has been challenged by their large thickness, impairing the applicability of such pursuits. Herein, an ultraporous architecture is designed to shorten Li+ transfer pathways by impregnating electrolyte‐affinitive poly (vinylidene fluoride‐co‐hexafluoropropylene) into ultralight ∼3 μm 3D‐polytetrafluoroethylene scaffold (abbreviated as UP3D). The UP3D separator with a porosity of 74% gives rise to 70% enhancement in Li+ transference and 77% reduction in Li+ transfer resistance (2.67 mΩ mm−1) and thus enables an ultrahigh Li+ flux of 22.7 mA cm−2, effectively alleviating Li+ concentration gradient across the separator. With the separator, the LiFePO4 half cell delivers a capacity of 118 mAh g−1 with an unparalleled capacity retention of 90% after 1000 cycles at 2 C, and a graphite || LiNi0.6Co0.2Mn0.2O2 pouch full cell delivers an areal energy density of 6.8 mWh cm−2 at 8.848 mA (1.4 mA cm−2) with a high cathode loading of 134.9 mg. Such results, together with the scalable production of the separator, reflect its promising potential in high‐flux battery applications of separators that require both ultrahigh porosity and reliability.